Frontal Lobe Seizure Presenting as Disorganised Behaviour to a Mental Health Service: A Case Report - Thilini Wickramarathna; Gayan Jayamaha; Miyuru Chandradasa; K.A.L.A. Kuruppuarachchi (BJPsych Open)
Aims: Epilepsy can present with a wide range of neuropsychiatric manifestations. A seizure episode may take the form of motor convulsions, complex abnormal behaviours or unusual subjective experiences.